Calculation of form factors, stringing and angular observables for the B → ω transition in the framework of the covariant quark model - Ilyassov М.N.; Issadykov А.N. (Recent Contributions to Physics, 2024)
The paper is devoted to the study of the B → ω transition in the framework of the covariant quark model, which is a theoretical approach to describe the hadron dynamics taking into account the quark structure. The aim of the work is to calculate the form factors for the B → ω transition in the whole range of the transmitted momentum q2, as well as to investigate and calculate the lepton channel decay branchings, forward-backward asymmetry, angular observables, longitudinal and transverse polarization for the decay B0 → ωl+l- (where l -e; m; t).. The scientific significance of the work lies in its contribution to the verification of the Standard Model and the possibility of discovering new physics related to the violation of lepton universality and other anomalies. The practical significance of the study is expressed in the possibility of using the results obtained for further experimental and theoretical studies in elementary particle physics. The methodology of the study is based on the covariant model of quarks, which describes hadrons as composite systems consisting of quarks and antiquarks interacting through effective vertex functions. The form factors are calculated using Fortran and Mathematica software, and their parameterization allows for further calculations of brenchings and angular observables. The results are in good agreement with available theoretical predictions. The calculations demonstrate the importance of the covariant quark model in the description of rare meson decays, confirming its applicability to the analysis of flavor-changing transitions. The contribution of this work to the field of knowledge is to provide new data to test theoretical models and to explore possible manifestations of new physics.